Implementasi Simple Additive Weighting Untuk Monitoring Aktivitas Perkuliahan Dengan Menggunakan Radio Frequency Identification - Darmawan, Ashari (Universitas Diponegoro, 2017)
Monitoring of learning activities has a very important role to improve the quality of education in University. The research Â aims to develop a monitoring system of learning activities in real time by using simple additive weighting and radio frequency identification technology.A simple additive weighting method is used to determine the weighting of each criterion involved in the system, while radio frequency identification technology is used electronically to identify and store learning activity information. Monitoring system built using learning activities data in the room and lecturer activities using radio frequency identification tag in real time. The results of the system include the recording of monitoring data of lecturing activities that produce lecturer attendance reports on each class in realÂ time, thus making efficient the time, effort and cost. The system also produces a ranking of lecturer discipline on each of the criteria that gives the difference of outcomes among the consistent lecturers present on schedule with inconsistent lecturers present on schedule. The results of monitoring of lecture activities can be used for university leaders as a decision-making material quickly based on actual data in real time to improve the quality of the learning process.